Work environment and low back pain: the influence of occupational activities. Issue 10 (October 1997) - Xu, Y; Bach, E; Orhede, E
Abstract : OBJECTIVES: To find associations between the prevalence of low back pain and occupational activities. METHODS: Interviews of a random sample of 5185 19-59 year old Danish employees analysed by logistic regression. RESULTS: Increased risks of low back pain were found for "vibration affecting the whole body" (odds ratio (OR) = 1.28), "physically hard work" (OR = 1.28), "frequently twisting or bending" (OR = 1.71), "standing up" (OR = 1.20), and "concentration demands" (OR = 1.28). In the analysis of dose-response relations between low back pain and the risk factors, the one year period prevalence increased with increasing exposure time during a working day to each of the risk factors. The prevalence proportion ratio for those reporting to be exposed for most of the working time were 1.30 for vibrations affecting the whole body, 1.54 for physically hard work, 1.48 for frequently twisting or bending, 1.29 for standing up, and 1.13 for concentration demands. These associations seemed to be stronger in the subset of subjects who worked for 37 hours or more per week. The population attributable fractions were 15.1% for frequently twisting or bending, 15.0% for standing up, 7.6% for concentration demands, and 4.4% for physically hard work. CONCLUSION: Vibrations affecting the whole body, physically hard work, frequently twisting or bending, standing up, and concentration demands proved to be risk factors for the occurrence of low back pain, even after controlling for age, sex, educational level, and duration of employment in a specific occupation.